2002
DOI: 10.1128/aac.46.4.1046-1052.2002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Low-Level Resistance to Azoles in Candida albicans Is Associated with Changes in Membrane Lipid Fluidity and Asymmetry

Abstract: The present study tracks the development of low-level azole resistance in in vitro fluconazole-adapted strains of Candida albicans, which were obtained by serially passaging a fluconazole-susceptible dose-dependent strain, YO1-16 (fluconazole MIC, 16 g ml ؊1 ) in increasing concentrations of fluconazole, resulting in strains YO1-32 (fluconazole MIC, 32 g ml ؊1 ) and YO1-64 (MIC, 64 g ml ؊1 ). We show that acquired resistance to fluconazole in this series of isolates is not a random process but is a gradually e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
112
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 34 publications
3
112
1
Order By: Relevance
“…CDR1-mediated drug resistance was susceptible to changes in membrane fluidity. 17,18) Our initial investigations showed that PLE can obviously reduce the expression of CDR1, 9) which may be influenced by imbalances in membrane lipid composition.…”
Section: Discussionmentioning
confidence: 99%
“…CDR1-mediated drug resistance was susceptible to changes in membrane fluidity. 17,18) Our initial investigations showed that PLE can obviously reduce the expression of CDR1, 9) which may be influenced by imbalances in membrane lipid composition.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators suggested that the altered membrane sterol pattern provided a common basis for antifungal resistance by preventing the binding of a drug and/or reducing its permeability (22). Recent reports also suggest that changes in the status of the membrane lipid phase and asymmetry could contribute to azole resistance in C. albicans (27,36). Moreover, microarray analyses revealed that the ERG2 (encoding the ergosterol biosynthesis pathway enzyme C-8 sterol isomerase) and CDR1 genes are upregulated in a planktonically grown fluconazole-resistant strain of C. albicans (46).…”
Section: Discussionmentioning
confidence: 99%
“…This ratio saturated/unsaturated FA increase suggested a modification in membrane composition and is in agreement with the study of Benyagoub et al (1996) which reported an increase in membrane fluidity on Fusarium oxysporum when exposed to an antifungal compound. In the same way, Kohli et al (2002) found an increase of membrane fluidity in Candida albicans treated with azoles. The disturbance in the unsaturated FA, especially the polyunsaturated C18:3, in the presence of propiconazole reminds an induction of lipid peroxidation.…”
mentioning
confidence: 54%